Knowledge of patients of Endoscopy Department on prophylaxis and treatment of large intestine neoplasm - Sapiełkin, Beata; Gotlib, Joanna (Nursing in the 21st Century, 2013)
KNOWLEDGE OF PATIENTS OF ENDOSCOPY DEPARTMENT ON PROPHYLAXIS AND TREATMENT OF LARGE INTESTINE NEOPLASM Introduction. According to the WHO, 7.5 million people (12.5% of the world population) die from a tumour every year. Large intestine carcinoma is the most frequent malignant neoplasm. Aim. The study aimed to analyse the level of knowledge of patients on the prophylaxis and treatment of neoplastic diseases of the large intestine. Materials and Methods. The study involved 114 patients participating in screening for large intestine neoplasm who were presenting themselves for colonoscopy to Endoscopy Department at One-Day Surgery Hospital due to medical indications. Voluntary and anonymous questionnaire studies, 35 questions, statistical analysis: Statsoft STATISTICA 10.0, Mann-Whitney U test, p<0.05. Results. A majority of the study participants know what the basic screening test for large intestine neoplasm is and could explain what the expression per rectum means. The majority of the study participants admitted that the level of their knowledge on prophylaxis and treatment of neoplastic diseases was insufficient. The study group indicated that the level of prophylaxis of neoplastic diseases of the large intestine in Poland is too low. Conclusions • The study participants had basic knowledge on the prophylaxis and treatment of neoplastic diseases of the large intestine. • The level of knowledge on the prophylaxis and treatment of neoplastic diseases of the large intestine was not gender-related among the study group. • The vast majority of the study participants declared that they gained information on preparation for colonoscopy from non-professional sources (e.g. the Internet); therefore physicians and nurses should more often instruct their patients in detail on the preparation process for prophylactic examinations and treatment course. • There is absolute requirement of patients for health education on neoplastic diseases of the large intestine conducted by specialists in health protection.